Aggressive Pituitary Tumors or Localized Pituitary Carcinomas: Defining Pituitary Tumors. Issue 2 (3rd March 2016) - Asa, Sylvia L.; Ezzat, Shereen
ABSTRACT: Pituitary tumors are common and exhibit a wide spectrum of hormonal, proliferative and invasive behaviors. Traditional classifications consider them malignant only when they exhibit metastasis. Patients who suffer morbidity and mortality from aggressive tumors classified as "adenomas" are denied support provided to patients with "cancers" and in many jurisdictions, these tumors are considered curiosities that do not warrant reporting in health registries. We propose use of the term "tumor" rather than "adenoma" to align with other neuroendocrine tumors. The features that can serve as diagnostic, prognostic and predictive markers are reviewed. Clinico-pathological and radiographic classifications provide important information and to date, no single biomarker has been able to offer valuable insight to guide the management of patients with pituitary tumors.